PENDIDIKAN KARAKTER PERSPEKTIF HADITS - Siregar, Septi Lastri; Lessy, Zulkipli (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Character education is a self building and a planned effort which aim to foster the character of students to strengthen their character. It is said that establishing character education can help students understand the values of human behavior related to God, self and others. Aim of this study is to explore good values connected character education establishment stemming from hadits (sayings of the Prophet). Method of this study is a literature review to investigate books containing hadits. In this effort, researchers tried to find meanings of the hadits connective to character building. Findings show that character education is needed, because education is not only aimed at fostering smart students, but education also aims to foster character and decency in everyday life. If students have character, then the nation will be good. Because students are the nation's next generation, they must educate their own character from an early age so that when they become the nation's successor they are not only smart, but also have character. Therefore, the inculcation of character values in students must start as early as possible, that is, the period in which children absorb a lot of future applied knowledge.